18F-Prostate-Specific Membrane Antigen and 18F-Fluorodeoxyglucose PET/CT Unmasked the Characteristics of Prostate Lymphoma: A Case Report and Literature Review - Fan Jiang; Junjie Fan; Junjie Fan; Hua Liang; XiaoYi Duan; Dalin He; Kaijie Wu (Frontiers in Medicine, 2022)
Prostate lymphoma (PL) is rarely observed and may be concurrently presented with prostate adenocarcinoma. Moreover, the appearance of PL on conventional imaging is similar with prostate adenocarcinoma. Thus, most of PL is diagnosed through prostate biopsy, or accidentally found in the specimens of surgery. Prostate-specific membrane antigen (PSMA) PET/CT has improved the management of prostate adenocarcinoma. While, the question regarding whether it benefits the discovery of the characteristics of PL is unknown. A 32-year-old man presented with worsening dysuria for 1 month, and the prostate-specific antigen (PSA) concentration was normal. While the pelvic MRI showed a mass in the prostate and multiple enlarged lymph nodes in the bilateral inguinal area. Then, the diagnosis of prostate adenocarcinoma was considered, but the serum PSA was normal and he was younger than most patients. So, 18F-PSMA PET/CT was then performed to further reveal the characteristics of the lesion and guide biopsy. However, there was no abnormal PSMA uptake in the lesion of the prostate and lymph nodes of the pelvic cavity and bilateral inguinal area. These lesions presented with increased glucose metabolism on fluorodeoxyglucose (FDG) PET/CT, and the prostate biopsy was then performed. PL was confirmed based on the results of the histopathologic examination, and the patient subsequently received systemic chemotherapy plus radiotherapy. Fortunately, the symptoms and the lesions completely disappeared after radiotherapy. The clinical symptoms of PL are atypical, and PL and adenocarcinoma may be concurrently presented. Moreover, distinguishing PL from prostate adenocarcinoma based on the appearance of conventional imaging is difficult. As opposed to prostate adenocarcinoma, a high FDG-avidity and low PSMA uptake by lymphoma either in the prostate or metastases are seen. So, PSMA PET/CT combined with FDG PET/CT can non-invasively identify the characteristics and origin of PL.